Considerații privind teatrul târgumureșean în perioada comunistă - Florea, Maria-Magdalena (Theatrical Research, 2021)
Considerations Regarding the Theatre of Târgu-Mureș in the Communist PeriodThere are a multitude of artistic directions that manifested themselves in the twentieth century in Romanian culture. This study presents, in short, the social and political framework in which the Târgumureș theater evolved during the Ceaușescu dictatorship. Thus, the period 1965-1971 is known as the period of cultural openness and political liberalization. The national veins of culture are rediscovered and revalued; art and cultural activities claim and gain relative autonomy from official policy directives, and ideological censorship becomes more permissive. Literature, theater, cinematography, cultural press, but also the visual arts, know a renewal of substance and performance achievements. After 1971, in the era of the cultural revolution imported from China and North Korea, the communist regime showed an increasing tendency to re-ideologize the cultural environment and tighten censorship. The political regime is gradually evolving towards a restalinization, by imposing an “ideological line” in culture and by the cult of the personality of the dictator Ceausescu. The effect of this ideological turn will prove to be culturally contradictory.